A formulation additive for simultaneously improving flue gas desulfurization efficiency and gypsum quality - Lv Lin (Association of the Chemical Engineers of Serbia, 2021)
The effects of different additives, including MgSO4, MnSO4, adipic acid, citric acid, benzoic acid, succinic acid and acrylic acid on SO2 removal from a limestone-gypsum wet flue gas desulfurization (FGD) system and gypsum characteristics were investigated. An optimized formulation additive for simultaneously improving flue gas desulfurization efficiency and gypsum quality was found. This formulation additive was successfully applied in an industrial-scale FGD system of a local coal power plant (600 MW, Shanghai Wujing Power Plant, China), and the gypsum quality was improved. The optimized formulation additive was acrylic acid, MnSO4 and citric acid mixed at a ratio of 1:1:2, which can simultaneously achieve an increased desulfurization efficiency of 97.02% and a low gypsum moisture content of 4.32%. Moreover, MnSO4 and acrylic acid were found to be most effective for improving SO2 removal, and citric acid contributed to gypsum particles with more uniform sizes and regular shapes, as well as good dewatering characteristics.